Kedudukan Hukum Anak Angkat sebagai Penerima Hibah dalam Sistem Hukum Indonesia - Nurul Fatimah; Agam Sulaksono; Ahmad Heru Romadhon (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Adoption is a legal act aimed at providing protection, well-being, and security for children. However, in legal practice in Indonesia, adopted children often face issues related to property rights, particularly regarding the acquisition of assets from their adoptive parents. Under Islamic law, adopted children are not considered heirs with a blood relationship to their adoptive parents and therefore do not automatically inherit. Consequently, a gift is the legal instrument used to provide economic protection to adopted children. This study aims to analyze the legal status of adopted children as recipients of gifts and to examine the validity of such gifts under Indonesian inheritance law. This study employs a normative legal method using a statutory approach and a conceptual approach. The results indicate that the legal status of adopted children as recipients of gifts is legally recognized provided they meet the applicable legal requirements under the Civil Code, the Compilation of Islamic Law, and other relevant regulations. However, the granting of a gift remains limited by the principle of protecting the rights of blood relatives through the concept of the “legitime portie” in the Civil Code and the maximum limit of one-third of the estate in the Compilation of Islamic Law. Thus, legal harmonization is necessary to ensure that gifts to adopted children provide legal certainty and equitable protection for all parties.